KOMPARASI PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE DAN TIPE CARD SORT TERHADAP KEMAMPUAN MENGHAFAL KOSAKATA BAHASA ARAB - Imamatul Islamiyah (Universitas Islam Negeri Mataram, 2023)
The purpose of this study was to determine whether there were differences in the ability to memorize Arabic vocabulary between the scramble type and the card sort type at MTs Negeri 6 Sleman. This study uses a comparative and quantitative experimental approach. Using methods such as documentation, tests, and observations to collect data for this study. Participants in this study were all students of class VII MTs Negeri 6 Sleman. After that, samples were taken from two classes, namely the experimental group I using the scramble type, class VII C, and the experimental group II using the card sort type, class VII E. The results showed that the ability of students in the experimental group I to memorize Arabic vocabulary was significantly different. significant with students in the experimental group II. card sorting type of experimental group II with scramble type. This difference can be seen from the normal post-test value of the exploration group I of 77.18 while the test group II got a normal post-test value of 85.33. Therefore, it can be concluded that the class using the scramble type and the class using the card sort type differ significantly from one another. Thus the card sort learning model can be used as a replacement technique to increase one's capacity in maintaining Arabic vocabulary